Activity of duodenal disaccharidases in relation to normal and abnormal mucosal morphology. Issue 7 (July 1990) - Langman, J M; Rowland, R
Abstract : Endoscopic duodenal biopsy specimens from 100 predominantly adult Caucasian patients under investigation for gastrointestinal symptoms were used to establish reference ranges for lactase, sucrase, and maltase in the duodenum. Duodenal and jejunal disaccharidase values were compared and the association between disaccharidase activity and morphology in the duodenum was examined. Mean lactase activities were about 40% lower in the duodenum compared with the jejunum; maltase was reduced to a lesser extent; and sucrase activities were much the same in the two sites. Lactase deficiency was found in 24 patients of whom 14 (58%) had duodenal disease. The presence of moderate to severe duodenal lesions was associated with a significant decrease in all disaccharidase activities, while only lactase was reduced in mild lesions. Twelve patients had normal lactase activity, despite the presence of duodenal disease. It is concluded that specific reference ranges for duodenal mucosal disaccharidase activity are required as this is less than that of jejunum. Reduced duodenal disaccharidase activity is usually but not invariably associated with morphological abnormality.